Effectiveness of cause‐related marketing for differential positioning of market entrant in developing market: An exploratory study in Indian context. Issue 2 (1st March 2017) - Shree, Deep; Gupta, Ankush; Sagar, Mahim
Abstract : Cause‐related marketing is being increasingly used for forging strong relation between the brand and the customer. It is primarily being used by the well‐established brands to further strengthen their position in the market as it leads to a positive image of the brand, and customers are more receptive towards such brands because they tend to provide them with tangible as well as intangible benefits. This study tends to identify the effectiveness of cause‐related marketing as a marketing tool for newly launched products in developing market of India, which has so far remained a less explored area. A sample of 150 consumers was taken, and case studies were undertaken for validating these findings. The findings suggest that cause‐related marketing campaigns, even at early stages of brand development, can lead to customer trial and differential positioning thus providing these new entrants with an opportunity to interact with the customers. The proposed framework can provide useful insights to brand managers to design cause‐related marketing campaigns for newly launched brands. The results and findings have been deduced from real‐time market research, and it can help in furthering research in the field of cause‐related marketing in India and other developing economies with similar market conditions.